Models for leaf area estimation in dwarf pigeon pea by leaf dimensions - Wartha, Cleiton Antonio; Pezzini, Rafael Vieira; Cargnelutti Filho, Alberto; Alves, Bruna Mendonça; Follmann, Diego Nicolau; Kleinpaul, Jéssica Andiara; Silveira, Daniela Lixinski (Bragantia, 2018)
This study aims to determine the most suitable model to estimate the leaf area of dwarf pigeon pea in function of the leaf central leaflet dimension. Six samplings of 200 leaves were performed in the first experiment, at 36, 42, 50, 56, 64, and 72 days after emergence (DAE). In the second experiment, seven samplings of 200 leaves were performed at 29, 36, 43, 49, 57, 65, and 70 DAE, totaling 2600 leaves. The length (L) and width (W) of the central leaflet were measured in all leaves composed by left, central, and right leaflets, the product of length times width (LW) was calculated, and the leaf area (Y – sum of left, central, and right leaflet areas) was determined by digital images. Linear, power, quadratic, and cubic models of Y as function of L, W, and LW were built using data from the second experiment. Leaves from the first experiment were used to validate the models. In dwarf pigeon pea, the linear (Ŷ = – 0.4088 + 1.6669x, R2 = 0.9790) is preferable, but power (Ŷ = 1.6097x1.0065, R2 = 0.9766), quadratic (Ŷ = – 0.3625 + 1.663x + 0.00007x2, R2 = 0.9790), and cubic (Ŷ = 0.7216 + 1.522x + 0.005x2 – 5E–05x3, R2 = 0.9791) models in function of LW are also suitable to estimate the leaf area obtained by digital images. The power model (Ŷ = 5.2508x1.7868, R2 = 0.95) based on the central leaflet width is less laborious because requires only one variable, but it presents accuracy reduction.
Keywords: Cajanus cajan (L.) Millsp; Modeling; Non-destructive method